Al-Al’âb al-Lughawiyyah wa Wazhâifuhâ fî Tanmiyyah Mahârât al-Fahm al-Qirâî ladâ Muta’allimiy al-‘Arabiyyah Lughah Tsâniyyah - Wahab Muhammed Jamiu (Postgraduate of IAIN Metro Lampung Indonesia, 2022)
The study aims to identify the importance of language games and their use developing reading comprehension skills, which are(reading speed, pronunciation accuracy, understanding the semantic meaning of words and sentences, ability to extract the meanings of words from within the text, ability to correct reading errors, ability to construct error sentences for students of third grade of primary school. In dealing with this issue, the current study adopts the applied descriptive approach in procedure and analysis in order to test the content of the success of language games in developing the reading comprehension skills of learners of Arabic as a second language, in particular at the elementary level. Because language games have educational and psychological benefits that are reflected in the students linguistic and personal performance. It helps them to receive lessons with fun, vitality and entertainment and its use shows children a high spirit of competition and participation, and accustoms them to spontaneity in using language in a natural way. Then the researcher concluded that the use of language games in teaching Arabic is a functional direction, and played an effective role in raising the level of students، comprehensive skills.